ОЗЕРНЫЙ МОРФОЛИТОГЕНЕЗ РАВНИН И ПРЕДГОРНЫХ ТЕРРИТОРИЙ СЕВЕРНОГО КАВКАЗА - Ефремов Ю.В.; Зеленский Н.И.; Макарь Е.В. (My University, 2003)
The conception of lacustrine morpholithogenesis is worked out. Conditions, factors, related processes of lake basin formation are discussed. Two stages of lacustrine morpholithogenesis - transgressive and regressive - are described.
Keywords: 551.435.3(=924.72)